Where I've been isn't where I'm going [compact disc] - Shaboozey, 1995- (American Dogwood ; Empire, 2024)
Rising multimedia artist Shaboozey intends to build his own world. Determined to carve his own lane in the alt-country/hip-hop space, he crafts a sound that pays homage to a cast of traditional Western influences, such as Bob Dylan, Lead Belly, Johnny Cash, and Leonard Cohen, while looking into the future of what the two genres have yet to introduce.